2016
DOI: 10.1158/1078-0432.ccr-15-1691
|View full text |Cite
|
Sign up to set email alerts
|

An Endothelial Gene Signature Score Predicts Poor Outcome in Patients with Endocrine-Treated, Low Genomic Grade Breast Tumors

Abstract: Purpose: The ability of vascular genes to provide treatment predictive information in breast cancer patients remains unclear. As such, we assessed the expression of genes representative of normal endothelial microvasculature (MV) in relation to treatment-specific patient subgroups.Experimental Design: We used expression data from 993 breast tumors to assess 57 MV genes (summarized to yield an MV score) as well as the genomic grade index (GGI) and PAM50 signatures. MV score was compared with CD31 staining by co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…We generated an MV score by summarizing the standardized mRNA expression levels for the vascular enriched genes as described. 24 By dichotomizing patients into 2 groups of equal size according to their MV scores, we found that a high MV score was significantly associated with shorter survival ( P = 0.0265, log-rank test) ( Fig. 2A , Supplementary Tables S7 and S8 ).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…We generated an MV score by summarizing the standardized mRNA expression levels for the vascular enriched genes as described. 24 By dichotomizing patients into 2 groups of equal size according to their MV scores, we found that a high MV score was significantly associated with shorter survival ( P = 0.0265, log-rank test) ( Fig. 2A , Supplementary Tables S7 and S8 ).…”
Section: Resultsmentioning
confidence: 90%
“…For each sample, the standardized values of all 456 vascular enriched genes were added to yield a microvasculature (MV) signature score (an MV score), as described. 24 …”
Section: Methodsmentioning
confidence: 99%
“…The study is designed such that 190 breast cancer patients that developed distant metastatic disease (cases) were selected from a consecutive series of individuals, and each closely matched by adjuvant therapy, age, and calendar period at diagnosis with three patients free from metastasis (controls) 28 . The gene signature for vCAFs correlated strongly to an endothelial metagene 27 and a microvasculature signature 29 within the dataset from the case–control study, whereas mCAFs instead were highly associated with a stroma-derived invasion signature 30 and a stroma-related treatment-predictive signature 31 (Fig. 5i ).…”
Section: Resultsmentioning
confidence: 96%
“…Six gene expression signatures were explored for their correlation with the CAF populations. These included endothelial/microvasculature signatures 27 , 29 , stroma-related signatures 27 , 30 , 31 , and a proliferation signature 32 . Gene signature scores were derived as the weighted averages of the expression values of the constituent signature genes, where the weight for each gene is +1 or −1 depending on the direction with the phenotype in the original publication.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we extended previous work of exploiting gene expression profiling approach for accurate detection of VEGF downstream biological activity, and designed a more stringent analytical protocol to identify and validate a reliable VEGF-dependent gene signature in preclinical tumor models and in human patients. Although the VDGs overlapped with previously developed VEGF-related signatures in general 22 26 , the refined gene list presented here was physiologically relevant on the basis of suitable in vivo models and integration of gene profiling results from two independent microarray platforms. Furthermore, we presented a detailed analysis of the VDGs in ovarian cancer by systematically interrogating TCGA HGS-OvCa expression data and four additional genome-wide transcriptome cohorts in the public domain.…”
Section: Discussionmentioning
confidence: 97%